Chronic mercury at low doses impairs white adipose tissue plasticity. (15th April 2019) - Rizzetti, Danize Aparecida; Corrales, Patricia; Piagette, Janaina Trindade; Uranga-Ocio, José Antonio; Medina-Gomez, Gema; Peçanha, Franck Maciel; Vassallo, Dalton Valentim; Miguel, Marta; Wiggers, Giulia Alessandra
Highlights: Hg long-term exposure to low concentration produces functional abnormalities in eWAT. Hg reduces adipocyte size and impairs glucose and lipid metabolism. Hg-induced eWAT disorders are related to PPARs, adipokines production and ER stress. Hg is a powerful environmental WAT disruptor that impairs adipocytes activity. Abstract: Introduction: The toxic effects of mercury (Hg) are involved in homeostasis of energy systems such as lipid and glucose metabolism, and white adipose tissue dysfunction is considered as a central mechanism leading to metabolic disorders. Objective: The aim of this study was to determine the effects of chronic inorganic Hg exposure at low doses on the lipid and glycemic metabolism. Methods: Male Wistar rats were divided into two groups and treated for 60 days with: saline solution, i.m. (Untreated) and mercury chloride, i.m. - 1 st dose 4.6 μg/kg, subsequent doses 0.07 μg/kg/day - (Mercury). Histological analyses, Hg levels measurement and GRP78, CHOP, PPARα, PPARγ, leptin, adiponectin and CD11 mRNA expressions were performed in epididymal white adipose tissue (eWAT). Glucose, triglycerides, total cholesterol and insulin plasma levels were also measured. Results: Hg exposure reduced the absolute and relative eWAT weights, adipocyte size, plasma insulin levels, glucose tolerance, antioxidant defenses and increased plasma glucose and triglyceride levels. In addition, CHOP, GRP78, PPARα, PPARγ, leptin and adiponectin mRNA expressions were increased in Hg-treated animals. No differences in Hg concentration were found in eWAT between the untreated and Hg groups. These results suggest that the reduction in adipocyte size is related to the impaired antioxidant defenses, endoplasmic reticulum (ER) stress, the disrupted PPARs and adipokines mRNA expression induced by the metal in eWAT. These disturbances possibly induced a decrease in circulating insulin levels, an imbalance between lipolysis and lipogenesis mechanisms in eWAT, with an increase in fatty acids mobilization, a reduction in glucose uptake and an activation of pro-apoptotic pathways, leading to hyperglycemia and hyperlipidemia. Conclusions: Hg is a powerful environmental WAT disruptor that influences signaling events and impairs metabolic activity and hormonal balance of adipocytes.